Nghiên cứu tổng hợp màu hồng san hồ (Pink coral) ZrSiO4 (alpha-Fe2O3)x cho đồ gốm sứ - Tường, Phan Văn; Quý Sơn, Lê Đình (Vietnam Journal of Chemistry, 2014)
The pink coral pigment has been synthesized from silica (quartz sand in Thua Thien Hue province), zirconia and iron (II) sulphate hetahydrate using a mixture of sodium fluoride and potassium cloride as mineralisers to lower the temperature of reaction. By measuring colour parameters (CIE, L*a*b*) of coloured glaze, using DTA and XRD methods we have studied the influence of mineralisers and firing temperature in pigment synthesized